STUDI EKSPERIMEN ANALISIS SIDE STEP ELEKTRODA TERHADAP KUALITAS ROUGNES PADA PROSES ELECTRICAL DISCHARGE MACHINE - Fajar Setiawan; Muhammad Irham Mahfud (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2018)
Electrical Discharge Machine (EDM) is increasingly being used in the manufacturing industry.Especially to overcome very hard material machinery, Mold made using EDM machine processtherefore the manufacturing time must be fast to become a finished product. In this research theauthors analyze the making of electrode into the tools in making mold by EDM machine. Sidestep of cutting speed of millions machine can be change by setting on CAM program, From theresults of this research to getting cavity with rougness 10S can using side step (previously 0,03)and get time cutting different 4 minutes or 28% faster.